The Challenges Of Research Production In Algeria –an Analytical Descriptive Study- - Kerouani, Mohamed Amine; Alhadidi, Malak (University of Eloued جامعة الوادي, 2024)
Abstract: Research production in research institutions is considered the real indicator of the countries progress and their societies sophistication, accordingly, we must pay great attention to it by undertaking the centers and institutions responsible for producing these scientific researches. So that we aim through this study to shed light on the reality of scientific research in Algeria and the most prominent challenges it faces.Through it, we have deliberately refered to the concept of scientific research, its characteristics, basics and types, in addition to highlighting and monitoring the challenges facing scientific research in Algeria to reach the mechanisms for promoting this field and overcoming the issue of weak scientific research, the importance of this study appears in that it is among the transformations taking place in the field of scientific research, which requires decision-makers to take a number of measures within a framework of a reform required by this sector to advance it.
Keywords: Researchproduction; Scientific research; Algeria; Challenges